It's not like I'm poor how working families make ends meet in a post-welfare world (Univ. of California Press, 2015)
This book chronicles the impact of the sweeping transformation of the social safety net that occurred in the mid-1990s. With the dramatic expansion of tax credits--a combination of the Earned Income Tax Credit and other refunds--the economic fortunes of the working poor have been bolstered as never before. 'It's Not Like I'm Poor' looks at how working families plan to use their annual windfall to build up savings, go back to school, and send their kids to college. But dreams of economic mobility are often dashed by the reality of making monthly ends meet on meager wages. - Provided by publisher